Long-term neuropsychologic outcome of pre-emptive mTOR inhibitor treatment in children with tuberous sclerosis complex (TSC) under 4 months of age (PROTECT), a two-arm, randomized, observer-blind, controlled phase IIb national multicentre clinical trial: study protocol - Jan H. Driedger; Julian Schröter; PROTECT-Study Group; Steffen Syrbe; Afshin Saffari (Orphanet Journal of Rare Diseases)
Abstract Background Tuberous sclerosis complex (TSC) is an autosomal dominant genetic disorder affecting multiple organ systems, with a prevalence of 1:6,760–1:13,520 live births in Germany. On the molecular level, TSC is caused by heterozygous loss-of-function variants in either of the genes TSC1 or TSC2, encoding the Tuberin-Hamartin complex, which acts as a critical upstream suppressor of the mammalian target of rapamycin (mTOR), a key signaling pathway controlling cellular growth and metabolism. Despite the therapeutic success of mTOR inhibition in treating TSC-associated manifestations, studies with mTOR inhibitors in children with TSC above two years of age have failed to demonstrate beneficial effects on disease-related neuropsychological deficits. It has thus been hypothesized, that the critical time window for mTOR inhibitors may lie in early infancy, before TSC-related symptoms such as early-onset epilepsy and infantile spasms as sign of disruptive brain maturation occur. No controlled prospective clinical trials have evaluated the effect of pre-symptomatic mTOR inhibitor therapy on neuropsychological manifestations in TSC patients under two years of age. Methods This two-arm, randomized, observer-blind, phase IIb national multicenter clinical trial aims at investigating the long-term neuropsychologic outcomes of pre-emptive mTOR inhibitor treatment in children diagnosed with TSC under four months of age. Sixty participants will be allocated to the trial with a 1:1 randomization ratio. The primary endpoint will be the neuropsychological outcome assessed by the cognitive scale of the Bayley Scales of Infant and Toddler Development III at 24 months of age compared to Standard of Care. Secondary endpoints include neuropsychologic outcomes at 12 months of age, seizure frequency, cardiac and cerebral tumor load, and safety assessments. Inclusion criteria are a definite TSC diagnosis and an age below four months at enrolment. The investigational medicinal product is sirolimus (Rapamune®), administered orally based on body surface area and surveilled by pharmacokinetic measurements, starting within the first four months of life and continuing until the second birthday. Conclusion This study addresses a critical gap in understanding the impact of pre-emptive mTOR inhibitor therapy on neuropsychologic outcomes in young TSC patients, aiming to improve overall patient outcomes and quality of life. EUCT number: 2022–502332-39–00, Registered 22/06/2023, https://euclinicaltrials.eu/search-for-clinical-trials/?lang=en&EUCT=2022-502332-39-00